Avaliação nutricional de pastagens temperadas associadas à leguminosa ou suplementação energética na dieta de bovinos - Lorensetti, Cassiano Albino (2016)
This study aims to evaluate the effect of diets: oats, ryegrass and supplement (AVAZS), oats, rye and vetch (AVAZE) and oats, ryegrass, vetch and supplement (AVAZES), consumption of nutrients, ruminal parameters and microbial protein synthesis in cattle. The experiment was conducted at the Universidade Tecnológica Federal do Paraná (UTFPR), Câmpus Dois Vizinhos, the Unit of Education and Research (UNEPE) - Cattle Court, during the months of June to December 2014. The experimental design was a double Latin square 3 x 3 (3 diets x 3 times), using six cattle steers, cannulated in the rumen, with average live weight of 350 kg. The forage samples were collected by the grazing simulation method. The consumption of grazing animals was determined using chromium oxide. The samples of rumen fluid were taken every two hours on the last day of each experimental period. Urine samples were taken in the last five days of each period. The consumption of non-fibrous carbohydrates (CCNF), the total digestible nutrients (CNDT), nitrogen consumption (CN), nitrogen retention (RN), the true digestibility of nitrogen (DVN), the digestibility of nitrogen (DN ) and nitrogen use efficiency (NUE) varied statistically (α <0.05) for cattle fed different diets. The pH and ammonia were higher (α<0.05) for the diets without supplement, since total sugars, peptides and α-amino were higher (α <0.05) in treatment satisfaction and legume supplement. The pH, ammonia and total sugars varied cubically regarding hours of the day, as the peptides and α-amino varied linearly. The values of microbial synthesis did not differ significantly (α> 0.05). Cattle kept in temperate grasslands associated with legumes and receiving supplementation have higher CCNF and CNDT. The non-supplemented cattle have higher CN, RN best, most DN greater DVN and better EUN. Animals exclusively grazing have pH and higher ruminal ammonia, since cattle receiving supplementation and intercropping with vetch have levels of total sugars, peptides and α-amino superior to other diets.